Increasing Students’ Vocabulary through English Movies at Second Grade Students in SMP Kristen 1 Dobo - Nussy, Wenssy Steva; Tiven, Punggulina Andawaty (MATAI: International Journal of Language Education, 2024)
The purpose of this study is to find out that watching English movies can increase students’ vocabulary mastery in SMP Kristen 1 Dobo and to know how the students respond to the implementation of English films to improve their vocabulary mastery in SMP Kristen 1 Dobo. The study used Classroom Action Research (CAR) as a research design. The study participants were second-grade students of SMP Kristen 1 Dobo, which consists of 25 students. The data collection techniques were tests and questionnaires. This research showed a development in the student’s vocabulary mastery after teaching English through English movies. This is shown from the mean at the end of cycle II, 81.12%, namely 25 students who got 69 points above. The total increase in the students' scores from the pre-test was 53%, the post-test I was 61.64%, and the post-test II was 81.12%. This means that the student's score has reached the target, and based on observation sheets and questionnaires for teachers and students, it shows that the implementation of the Watching English movie is effective in students' vocabulary mastery.